Contemplation on wheat vernalization - Milec, Zbyněk; Strejčková, Beáta; Šafář, Jan (Frontiers in Plant Science, 2023)
Vernalization is a period of low non-freezing temperatures, which provides the competence to flower. This mechanism ensures that plants sown before winter develop reproductive organs in more favourable conditions during spring. Such an evolutionary mechanism has evolved in both monocot and eudicot plants. Studies in monocots, represented by temperate cereals like wheat and barley, have identified and proposed the VERNALIZATION1 (VRN1) gene as a key player in the vernalization response. VRN1 belongs to MADS-box transcription factors and is expressed in the leaves and the apical meristem, where it subsequently promotes flowering. Despite substantial research advancement in the last two decades, there are still gaps in our understanding of the vernalization mechanism. Here we summarise the present knowledge of wheat vernalization. We discuss VRN1 allelic variation, review vernalization models, talk VRN1 copy number variation and devernalization phenomenon. Finally, we suggest possible future directions of the vernalization research in wheat.